Modelling flow and mass transfer inside spacer-filled channels for reverse osmosis membrane modules - Chong, Yie Kai; Liang, Yong Yeow; Lau, Woei Jye; Adolfo, Gustavo (Elsevier, 2022)
Mathematical modelling is widely used to simulate the hydrodynamics and mass transport in the spacer-filled channels of reverse osmosis spiral-wound membrane modules. This chapter reviews the recent research using one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) models to simulate the fluid flow and solute transport conditions inside channels with feed spacers. With significant improvements in semiconductor technology in recent years, 2D and 3D CFD-based modelling of spacer-filled channels has become more and more common. This chapter also reviews the recent modelling studies within unsteady shear strategies, novel spacer geometries, and fouling reduction.